2007
DOI: 10.1094/phyto-97-8-0997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Urediniospore Germination, Germ Tube Growth, and Initiation of Infection in Soybean by Phakopsora Isolates

Abstract: Temperature is a critical factor in plant disease development. As part of a research program to determine how specific environmental variables affect soybean rust, we determined temperature effects on urediniospore germination and germ tube growth of four isolates of Phakopsora pachyrhizi, one each from Brazil, Hawaii, Taiwan, and Zimbabwe, and an isolate of P. meibomiae from Puerto Rico, collected over a 25-year period. Also compared were the effects of temperature during a night dew period on initiation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 16 publications
1
17
0
7
Order By: Relevance
“…Voltando ao primeiro nó e considerando a subárvore à direita, há um significativo maior número de casos de não ocorrência (2001 casos) do que ocorrência (305 casos), evidenciando o efeito prejudicial das baixas temperaturas (<15 °C) na germinação de esporos e eventos de penetração nas plantas (MARCHETTI et al, 1976;KOCHMAN, 1979;ALVES et al, 2006;BONDE et al, 2007). O nó-folha 31 foi o que classificou o maior número de casos de não ocorrência (636) e teve sua origem a partir do nó 24, que determinou o limiar de 27,1 °C para a média da temperatura máxima, no período de 20 dias antes do evento.…”
Section: Figura 2 Relação Entre O Número Mínimo De Objetos Por Folhaunclassified
See 1 more Smart Citation
“…Voltando ao primeiro nó e considerando a subárvore à direita, há um significativo maior número de casos de não ocorrência (2001 casos) do que ocorrência (305 casos), evidenciando o efeito prejudicial das baixas temperaturas (<15 °C) na germinação de esporos e eventos de penetração nas plantas (MARCHETTI et al, 1976;KOCHMAN, 1979;ALVES et al, 2006;BONDE et al, 2007). O nó-folha 31 foi o que classificou o maior número de casos de não ocorrência (636) e teve sua origem a partir do nó 24, que determinou o limiar de 27,1 °C para a média da temperatura máxima, no período de 20 dias antes do evento.…”
Section: Figura 2 Relação Entre O Número Mínimo De Objetos Por Folhaunclassified
“…Estudos sobre fases específicas do ciclo da doença proporcionaram um conhecimento básico e importante sobre a epidemiologia da ferrugem asiática da soja (MARCHETTI et al, 1976;KOCHMAN, 1979;ALVES et al, 2006;BONDE et al, 2007). Diversos modelos e sistemas de alerta de ferrugem asiática foram desenvolvidos, em sua maioria baseados em abordagens mecanística ou empírica, ou seja, por meio de ajustes de modelos aos dados obtidos em ambiente controlado ou em condições de campo (ver revisão sobre os modelos em DEL PONTE et al, 2006a).…”
Section: Introductionunclassified
“…Also, in a study from India, minimum, optimum and maximum temperatures for spore germination were 20, 25 and 30ºC, respectively (Singh & Thapliyal, 1977). In a recent study, a comparison was made among four isolates of P. pachyrhizi, one each from Taiwan, Zimbabwe, Hawaii, and Brazil to determine the effect of temperature on urediniospore germination and germ-tube growth (Bonde et al, 2007). The authors showed that all isolates behave similarly as to how temperature affects urediniospore germination, germ-tube growth and initiation of infection, in spite of the fact that they had been collected from different parts of the world over a period of 21-year period.…”
Section: Meteorological Factors Affecting Epidemiological (Monocyclicmentioning
confidence: 99%
“…The first step in infection is urediniospore germination, which is influenced by environmental factors that include temperature (Bonde et al, 2007;Joseph and Hering, 1997;Tapsoba and Wilson, 1997) and duration of leaf surface wetness (Joseph and Hering, 1997). Most spores are extremely sensitive to even a few hours of intense sunlight (Maddison and Manners, 1972).…”
Section: Resultsmentioning
confidence: 99%